A Journey of Challenges and Victories: A Bibliometric Worldview of Nanomedicine since the 21st Century - Wang, Jingyu; Zhao, Wenling; Zhang, Zhao; Liu, Xingzi; Xie, Tong; Wang, Lan; Xue, Yuzhou; Zhang, Yuemiao (Advanced materials (Weinheim), 2024)
Nanotechnology profoundly affects the advancement of medicine. Limitations in diagnosing and treating cancer and chronic diseases promote the growth of nanomedicine. However, there are very few analytical and descriptive studies regarding the trajectory of nanomedicine, key research powers, present research landscape, focal investigative points, and future outlooks. Herein, articles and reviews published in the Science Citation Index Expanded of Web of Science Core Collection from first January 2000 to 18th July 2023 are analyzed. Herein, a bibliometric visualization of publication trends, countries/regions, institutions, journals, research categories, themes, references, and keywords is produced and elaborated. Nanomedicine‐related academic output is increasing since the COVID‐19 pandemic, solidifying the uneven global distribution of research performance. While China leads in terms of publication quantity and has numerous highly productive institutions, the USA has advantages in academic impact, commercialization, and industrial value. Nanomedicine integrates with other disciplines, establishing interdisciplinary platforms, in which drug delivery and nanoparticles remain focal points. Current research focuses on integrating nanomedicine and cell ferroptosis induction in cancer immunotherapy. The keyword “burst testing” identifies promising research directions, including immunogenic cell death, chemodynamic therapy, tumor microenvironment, immunotherapy, and extracellular vesicles. The prospects, major challenges, and barriers to addressing these directions are discussed. A meticulous and extensive bibliometric analysis of nanomedicine publications over a 23‐year period (2000‐2023) is presented. This study covers publication trends, research powers, keywords, references, subject classifications, research themes, and journals. This investigation reveals the field's evolution, current state, frontiers, and emerging trends. Valuable insights will inspire researchers in diverse industries, enriching their refined comprehension of nanomedicine research.